Implementation of Kano Methods to Service Quality Improved at PT. Pos Indonesia - Suhartini, Suhartini; Prabowo, R; Hariastuti, N L P; Rafsanjani, A D (IPTEK Journal of Proceedings Series, 2018)
PT. Pos Indonesia is a state-owned company engaged in the field of receipt and delivery of goods which was first established in 1746. Frequent problems with freight forwarding services, especially PT. Pos Indonesia is a lack of competitiveness of companies with similar companies, especially private ones. This is because companies are less able to understand the desires and expectations of consumers so that they lose trust and loyalty from consumers. From these problems the purpose of this study was to find a solution using a canoe model in an effort to find improvement proposals to improve quality at PT. Indonesian post. From the research that has been done, there are 4 canoe categories on 11 variables studied. In the category of Must-be, the customer variable is comfortable and strategic location, One Dimensional, namely variable comfortable waiting place, adequate supporting facilities, timely delivery, appropriate price, fast service time and Attractive item security are only professional employee variables, and Indifferent is a lot of service and promotion in various media.